Nonalcoholic Fatty Liver Disease and Diabetes Mellitus Are Associated With Post–Transjugular Intrahepatic Portosystemic Shunt Renal Dysfunction: An Advancing Liver Therapeutic Approaches Group Study. Issue 3 (2nd January 2021) - Ge, Jin; Lai, Jennifer C.; Boike, Justin Richard; German, Margarita; Jest, Nathaniel; Morelli, Giuseppe; Spengler, Erin; Said, Adnan; Lee, Alexander; Hristov, Alexander; Desai, Archita P.; Junna, Shilpa; et al.
Abstract : Transjugular intrahepatic portosystemic shunt (TIPS) is an effective intervention for portal hypertensive complications, but its effect on renal function is not well characterized. Here we describe renal function and characteristics associated with renal dysfunction at 30 days post‐TIPS. Adults with cirrhosis who underwent TIPS at 9 hospitals in the United States from 2010 to 2015 were included. We defined "post‐TIPS renal dysfunction" as a change in estimated glomerular filtration rate (ΔeGFR) ≤−15 and eGFR ≤ 60 mL/min/1.73 m 2 or new renal replacement therapy (RRT) at day 30. We identified the characteristics associated with post‐TIPS renal dysfunction by logistic regression and evaluated survival using adjusted competing risk regressions. Of the 673 patients, the median age was 57 years, 38% of the patients were female, 26% had diabetes mellitus, and the median MELD‐Na was 17. After 30 days post‐TIPS, 66 (10%) had renal dysfunction, of which 23 (35%) required new RRT. Patients with post‐TIPS renal dysfunction, compared with those with stable renal function, were more likely to have nonalcoholic fatty liver disease (NAFLD; 33% versus 17%; P  = 0.01) and comorbid diabetes mellitus (42% versus 24%; P  = 0.001). Multivariate logistic regressions showed NAFLD (odds ratio [OR], 2.04; 95% confidence interval [CI], 1.00‐4.17; P  = 0.05), serum sodium (Na; OR, 1.06 per mEq/L; 95% CI, 1.01‐1.12; P  = 0.03), and diabetes mellitus (OR, 2.04; 95% CI, 1.16‐3.61; P  = 0.01) were associated with post‐TIPS renal dysfunction. Competing risk regressions showed that those with post‐TIPS renal dysfunction were at a higher subhazard of death (subhazard ratio, 1.74; 95% CI, 1.18‐2.56; P  = 0.01). In this large, multicenter cohort, we found NAFLD, diabetes mellitus, and baseline Na associated with post‐TIPS renal dysfunction. This study suggests that patients with NAFLD and diabetes mellitus undergoing TIPS evaluation may require additional attention to cardiac and renal comorbidities before proceeding with the procedure.